Design of a 324 MHz 200 kW CW Waveguide-to-Coaxial Adaptor for Radio Frequency Quadrupole Microwave System. (10th December 2020) - Yan, Xinsheng; Zhao, Lianmin; Ding, Bojiang; Xu, Weiye; Jia, Hua; Wu, Zege; Liu, Fukun
Abstract : A 324 MHz 200 kW waveguide-to-coaxial adaptor has been designed and fabricated for a microwave coupler in a radio frequency quadrupole system. Optimization of the adaptor is performed by the numerical study and experimental test. High-power measurements show that the reflection coefficient of the adaptor is less than −30 dB at the RFQ operating frequency, and there is no breakdown in the 228 kW pulse test. The measurement results are consistent with the simulation results, indicating that the adaptor has good high-power transmission performance. This work provides theoretical and experimental bases for a rectangular-to-coaxial adaptor design, especially in high-power steady-state operation.